Association between schoolbag weight and back pain among primary schoolchildren in Kajang, Selangor - Shuhaimi, Shurul Azwa; Abdul Rahman, Haliza (Malaysian Public Health Physicians' Association, 2020)
These days, there is a growing concern that schoolchildren are carrying too heavy school back on their backs. The use of a back pack is the most important factor causing low back pain among students. Thus, a cross sectional study was conducted on 81 schoolchildren from two different types of primary school in Kajang, Selangor. The objective of this paper is to determine the association between schoolbag weight and back pain among primary schoolchildren in Kajang, Selangor. For the method, respondents’ body weight and their schoolbag weight were measured using the electronic body composition OMRON and KERN weighing scale respectively, while the height was measured using Body Meter Seca 208cm. Back pain in the past one week was assessed using questionnaire, adapted from previous studies. This studied involving 81 primary schoolchildren from two types of school which were government and private school. 74.1% of schoolchildren had the schoolbag weight more than 10% of their body weight. 32.1% of schoolchildren reported having back pain and 21.0% of them were female respondents. Back pain was detected in 24.7% government schoolchildren and 7.4% private schoolchildren. There was significant association between back pain and; relative weight (x2=9.720, p=0.002) and types of school (x2=4.949, p=0.026). As conclusion, schoolchildren that carry schoolbag heavier than that generally recommended which is not more than 10% of body weight will experienced the back pain.